Subnational Autonomy and Political Islam: A Comparative Analysis of Aceh, Bangsamoro, and Patani - Ziegenhain, Patrick (Graduate School of UIN Syarif Hidayatullah Jakarta, 2025)
This article examines the different dynamics between subnational autonomy and political Islam in three distinct Southeast Asian contexts from a comparative perspective. The three cases studies concern Aceh (Indonesia), Bangsamoro (the Philippines), and Patani (Thailand). Through an analysis of historical grievances, political movements, peace agreements, and legal frameworks, the study reveals that the pursuit of self-governance is deeply intertwined with Islamic identity and aspirations. The paper aims to identify commonalities in the respective conflict trajectories and the centrality of Islam herein. However, it also highlights significant differences in the extent and nature of autonomy achieved, the specific objectives of political Islam, and the outcomes of the respective peace processes. As a general target, the study would like to offer insights into the broader implications for understanding state-minority relations and conflict resolution in Southeast Asia, which is known to be a religiously diverse region.